2021
DOI: 10.1038/s41598-021-89983-x
|View full text |Cite
|
Sign up to set email alerts
|

DHHC21 deficiency attenuates renal dysfunction during septic injury

Abstract: Renal dysfunction is one of the most common complications of septic injury. One critical contributor to septic injury-induced renal dysfunction is renal vascular dysfunction. Protein palmitoylation serves as a novel regulator of vascular function. Here, we examined whether palmitoyl acyltransferase (PAT)-DHHC21 contributes to septic injury-induced renal dysfunction through regulating renal hemodynamics. Multispectral optoacoustic imaging showed that cecal ligation and puncture (CLP)-induced septic injury cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In recent studies, we identified a significantly increased plasma level of EVs in patients and animals with trauma and sepsis, correlating with exacerbated proinflammatory response and cellular injury ( Beard et al, 2016 ). We also observed greatly increased palmitoylation and DHHC21 activity under inflammatory conditions ( Beard et al, 2016 ; Yang et al, 2021 ). DHHC21, unlike other DHHCs, is localized in plasma membrane, which allows it to dynamically regulate the function of many plasma membrane-associated proteins involved in EV generation, such as G protein-coupled receptors, G proteins, and phospholipases ( Beard et al, 2016 ; Fan et al, 2020 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In recent studies, we identified a significantly increased plasma level of EVs in patients and animals with trauma and sepsis, correlating with exacerbated proinflammatory response and cellular injury ( Beard et al, 2016 ). We also observed greatly increased palmitoylation and DHHC21 activity under inflammatory conditions ( Beard et al, 2016 ; Yang et al, 2021 ). DHHC21, unlike other DHHCs, is localized in plasma membrane, which allows it to dynamically regulate the function of many plasma membrane-associated proteins involved in EV generation, such as G protein-coupled receptors, G proteins, and phospholipases ( Beard et al, 2016 ; Fan et al, 2020 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 53%
“…We also observed greatly increased palmitoylation and DHHC21 activity under inflammatory conditions ( Beard et al, 2016 ; Yang et al, 2021 ). DHHC21, unlike other DHHCs, is localized in plasma membrane, which allows it to dynamically regulate the function of many plasma membrane-associated proteins involved in EV generation, such as G protein-coupled receptors, G proteins, and phospholipases ( Beard et al, 2016 ; Fan et al, 2020 ; Yang et al, 2021 ). In the present study, we sought to determine if DHHC21-mediated palmitoylation affects EV production, cargo content, and function during sepsis.…”
Section: Introductionmentioning
confidence: 53%
“…Our results demonstrate that reducing MLKL and pMLKL acylation via zDHHC21 inactivation restores membrane integrity during necroptosis (Figure 3E). Previous studies showed that zDHHC21 depletion ameliorated septic injury in renal reperfusion 32 and barrier dysfunction in endothelial inflammation 33 , suggesting an important role for zDHHC21 in membrane integrity. Based on these, we decided to focus on the involvement of zDHHC21 in the fate of pMLKL, the functional form of MLKL in necroptosis.…”
Section: Resultsmentioning
confidence: 96%
“…Our results demonstrate that reducing MLKL and pMLKL acylation via zDHHC21 inactivation restores membrane integrity during necroptosis (Figure E). Previous studies showed that zDHHC21 depletion ameliorated septic injury in renal reperfusion and barrier dysfunction in endothelial inflammation, suggesting an important role for zDHHC21 in membrane integrity. Based on these, we decided to focus on the involvement of zDHHC21 in the fate of pMLKL, the functional form of MLKL in necroptosis.…”
Section: Resultsmentioning
confidence: 99%